Impact of asthma on bronchiectasis severity and risk of exacerbations. (15th February 2022) - Ferri, Sebastian; Crimi, Claudia; Campisi, Raffaele; Cacopardo, Giulia; Paoletti, Giovanni; Puggioni, Francesca; Crimi, Nunzio; Heffler, Enrico
Abstract: Objective: Asthma is a frequent comorbidity of bronchiectasis, with possible implications for exacerbation and severity. We investigated the clinical impact of asthma on bronchiectasis in terms of disease severity and exacerbation risk. Methods: We collected demographic, clinical, and functional characteristics of patients with a confirmed diagnosis of bronchiectasis. All patients were investigated for concomitant diagnosis of asthma. The Bhalla score was used to assess radiological severity of bronchiectasis, and the Bronchiectasis Severity Index (BSI) was used to assess the clinical severity. Blood and sputum samples were collected to assess blood cell count, erythrocyte sedimentation rate, c-reactive protein, immunological status (IgA, IgE, IgM, IgG, and IgG subclasses), and microbiological analysis. Results: A total of 106 patients were enrolled in the study; 30.2% had concomitant asthma and were characterized by higher frequency of bronchiectasis exacerbation, despite higher Bhalla score and lower BSI compared to patients without asthma. Pseudomonas aeruginosa was more frequently isolated from the sputum of bronchiectasis patients without asthma. Total serum IgG, IgG1, and IgG3 were lower in patients with asthma. Blood eosinophils and exhaled nitric oxide were higher in patients with associated asthma. The presence of asthma and presence of Pseudomonas in sputum were the only significant determinants of frequent exacerbations in a binary logistic regression analysis. Conclusion: The coexistence of asthma and bronchiectasis is associated with an independent increase in the risk of bronchiectasis exacerbation despite lower radiological and clinical severity indexes. Asthmatic airway inflammation could promote an enhanced "Cole's Cycle" that is responsible for a higher frequency of exacerbations.